Uncovering Factors Affecting Employee Performance in the Manufacturing Industry: Work Stress, Workload, and Work Environment - STP, Audy; Novita, Sofia; Sulistiyowati, Lisa Harry (Jurnal Manajemen (Edisi Elektronik), 2025)
Employee performance in the manufacturing industry is the key to the company’s success, influenced by individual abilities as well as factors such as work stress, workload, and the interrelated work environment. Given the significance of these factors, the study aims to identify how they affect employee performance in the manufacturing sector. A quantitative approach was used, with a simple random sampling method selecting 110 respondents from a population of 183 in the production section. Data was collected through a Likert scale-based questionnaire consisting of 42 statements, reflecting indicators for each variable. SPSS version 25 was used to analyze the data, including validity and reliability tests, hypothesis testing using the t-test, and classical assumption tests such as normality and multicollinearity. The normality test results indicate that the data is normally distributed (Kolmogorov-Smirnov test value = 0.093, p > 0.05), and the multicollinearity test confirms no excessive relationship between the independent variables (tolerance > 0.10, VIF < 10). Hypothesis testing reveals that work stress (X1) and workload (X2) have insignificant negative effects on employee performance (t = -1.697 and t = -1.865, p > 0.05), while the work environment (X3) has a small but positive effect (t = 1.664, p > 0.05), though not statistically significant. These results suggest that while stress and workload do not significantly hinder performance, a supportive work environment may contribute positively, albeit marginally, to employee productivity.